Genetic interaction of hnRNPA2B1 and DNAJB6 in a Drosophila model of multisystem proteinopathy - Li, Songqing (Hum Mol Genet, 2016)
Adult-onset inherited myopathies with similar pathological features, including hereditary inclusion body myopathy (hIBM) and limb-girdle muscular dystrophy (LGMD), are a genetically heterogeneous group of muscle diseases. It is unclear whether these inherited myopathies initiated by mutations in distinct classes of genes are etiologically related. Here, we exploit a genetic model system to establish a mechanistic link between diseases caused by mutations in two distinct genes, hnRNPA2B1 and DNAJB6. Hrb98DE and mrj are the Drosophila melanogaster homologs of human hnRNPA2B1 and DNAJB6, respectively. We introduced disease-homologous mutations to Hrb98DE, thus capturing mutation-dependent phenotypes in a genetically tractable model system. Ectopic expression of the disease-associated mutant form of hnRNPA2B1 or Hrb98DE in fly muscle resulted in progressive, age-dependent cytoplasmic inclusion pathology, as observed in humans with hnRNPA2B1-related myopathy. Cytoplasmic inclusions consisted of hnRNPA2B1 or Hrb98DE protein in association with the stress granule marker ROX8 and additional endogenous RNA-binding proteins (RBPs), suggesting that these pathological inclusions are related to stress granules. Notably, TDP-43 was also recruited to these cytoplasmic inclusions. Remarkably, overexpression of MRJ rescued this phenotype and suppressed the formation of cytoplasmic inclusions, whereas reduction of endogenous MRJ by a classical loss of function allele enhanced it. Moreover, wild-type, but not disease-associated, mutant forms of MRJ interacted with RBPs after heat shock and prevented their accumulation in aggregates. These results indicate both genetic and physical interactions between disease-linked RBPs and DNAJB6/mrj, suggesting etiologic overlap between the pathogenesis of hIBM and LGMD initiated by mutations in hnRNPA2B1 and DNAJB6.